The Role of Islamic Religious Education Teachers in Spreading the Ideology of Islamic Moderation - Kohar, Muhamad Nafi; Majid, Abdul (International Journal Labs, 2023)
One of the problems nowadays is the low level of tolerance between people and also the low level of moderate attitudes possessed by humans. This cannot be separated from the role of teachers in schools, they do not monitor the development of students, even though the responsibility of a teacher is not only responsibility for knowledge, but what is more important is the responsibility for morals, ethics, character and personality of students. Regarding these four things, it will not be well formed if a teacher only transfers his values without making any effort to educate, develop and guide children and provide an understanding of how important it is to have a moderate and tolerant attitude. Writing this thesis under the title The Role of Islamic Religious Education Teachers in Spreading the Ideology of Islamic Moderation (Case Study at SMA Takhassus Al-Qur'an Wonosobo), aims to determine the role of teachers in spreading the ideology of Islamic moderation and to find out what material content is related to the ideology. Islamic moderation at Takhassus Al-Qur'an High School, and also what problems teachers face in spreading the ideology of Islamic moderation at Takhassus Al-Qur'an High School. The method used in this research is a qualitative type of research, with descriptive analysis of data produced through observations, interviews and also documentation at the place used as the research object The results of the analysis from writing this thesis are that the role of Islamic religious education teachers at Takhassus Al-Qur'an High School in spreading the ideology of Islamic moderation has a high role, namely by providing understanding through learning, providing opportunities for students to be directly involved in society at the same time. show a mature, tolerant and moderate attitude, and also provide concrete examples to students of how to be tolerant and moderate. From the results of the analysis, the author also found several material contents related to understanding how important it is to have a tolerant and moderate attitude. Then, in order to spread the ideology of Islamic moderation at Takhassus Al-Qur'an High School, Islamic education teachers only have a few problems, namely those related to learning methods and also the learning media used in each lesson, but in general, Islamic education teachers at Takhassus Al High School -The Qur'an does not have significant obstacles related to providing students with an understanding of Islamic moderation.